Emerging Issues of Australia's Sub-Antarctic Islands: Macquarie Island and Heard Island and McDonald Islands - Kriwoken, LK; Holmes, ND (Federation Press, 2007)
Macquarie Island (Macquarie) and Heard Island and McDonald Islands (HIMI) are spectacular, remote Australian sub-Antarctic islands located in the Southern Ocean. Macquarie and HIMI are home to an abundant and diverse array of unique sub-Antarctic wildlife. The vastness of the Southern Ocean and the isolation of these islands mean they provide crucial habitat for fauna, flora and microbial life. On Macquarie and HIMI3.5 and 1.3 million seabirds annually breed and moult, largely represented by five penguin species.